2005
DOI: 10.2174/138955705774329555
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids and Cancer

Abstract: Marijuana has been used in medicine for millennia, but it was not until 1964 that delta9-tetrahydrocannabinol (delta9-THC), its major psychoactive component, was isolated in pure form and its structure was elucidated. Shortly thereafter it was synthesized and became readily available. However, it took another decade until the first report on its antineoplastic activity appeared. In 1975, Munson discovered that cannabinoids suppress Lewis lung carcinoma cell growth. The mechanism of this action was shown to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 68 publications
(174 reference statements)
0
35
0
Order By: Relevance
“…Furthermore, we have shown that THC inhibited the EGF-induced phosphorylation of ERK1/2, JNK1/2 and AKT. Although THC exhibits psychoactive effects mediated by neuronal CB 1 receptors (Piomelli, 2003), the adverse side effects tend to wane with continuous use (Kogan, 2005). Our findings suggest a therapeutic use of cannabinoids like THC in the treatment of EGFRoverexpressing, aggressive and chemotherapy-resistant lung cancers.…”
Section: Thc Inhibits Nsclc Metastasis and Growthmentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, we have shown that THC inhibited the EGF-induced phosphorylation of ERK1/2, JNK1/2 and AKT. Although THC exhibits psychoactive effects mediated by neuronal CB 1 receptors (Piomelli, 2003), the adverse side effects tend to wane with continuous use (Kogan, 2005). Our findings suggest a therapeutic use of cannabinoids like THC in the treatment of EGFRoverexpressing, aggressive and chemotherapy-resistant lung cancers.…”
Section: Thc Inhibits Nsclc Metastasis and Growthmentioning
confidence: 77%
“…Previous studies have demonstrated tumor-promoting or antineoplastic effects of THC (Munson et al, 1975;Kogan, 2005). However, cannabinoid effects on the EGFR-mediated growth and motility of lung cancer cells have not been characterized to our knowledge.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the precise pathways through which these molecules produce an antitumor effect has not been yet fully characterized, also because their mechanism of action appears to be dependent on the type of tumor cell under study. It has been reported that cannabinoids can act through different cellular mechanisms, e.g., by inducing apoptosis, cell-cycle arrest, or cell growth inhibition, but also by targeting angiogenesis and cell migration [7] [19]. Furthermore, the antitumor effects of plant, synthetic and endocannabinoids can be mediated by activation of either CB1 [20] or CB2 receptors or both [21] [22].…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, suggests a therapeutic potential in the modulation of the ECS. Endocannabinoids and their synthetic analogs have important effects on the cardiovascular system, including complex mechanisms affecting the vasculature and the myocardium, but also autonomic outflow regulation through sites of action in the central and peripheral nervous system 43, 66, 69, 70. Modulation of the ECS has been suggested as a therapeutic avenue for various disorders of the cardiovascular system ranging from atherosclerosis and restenosis, hypertension, cirrhotic cardiomyopathy; to myocardial infarction, and chronic heart failure 42…”
Section: The Ecs In Cvd Pathologymentioning
confidence: 99%